2021
DOI: 10.3892/ol.2021.12594
|View full text |Cite
|
Sign up to set email alerts
|

Role of MALAT1 in gynecological cancers: Pathologic and therapeutic aspects (Review)

Abstract: Gynecological cancers, including breast, ovarian, uterine, vaginal, cervical and vulvar cancers are among the major threats to modern life, particularly to female health. Long non-coding RNAs (lncRNAs) play critical roles in normal development of organisms, as well as the tumorigenesis process, and metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a large infrequently spliced lncRNA, which have been implicated in different gynecological cancers. MALAT1 is overexpressed in breast, ovarian, cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Following its initial identification in a screen for transcripts associated with the metastasis and survival of non-small cell lung cancer, subsequent investigations have demonstrated that the primary gene sequence of MALAT1 spans over 8 Kb and exhibits a high degree of conservation across 33 different mammalian species (Zhang et al 2017). The transcript length of this gene is estimated to be around 7000 base pairs in humans and approximately 6700 base pairs in mice (Qiao et al 2021). The transcription of MALAT1 is mediated by RNA polymerase II, and the promoter region of this gene is characterized by an open chromatin architecture, which has been demonstrated in various high-throughput studies and DNAase sensitivity assays (Arratia et al 2023).…”
Section: Malat1 Structure and Functionmentioning
confidence: 99%
“…Following its initial identification in a screen for transcripts associated with the metastasis and survival of non-small cell lung cancer, subsequent investigations have demonstrated that the primary gene sequence of MALAT1 spans over 8 Kb and exhibits a high degree of conservation across 33 different mammalian species (Zhang et al 2017). The transcript length of this gene is estimated to be around 7000 base pairs in humans and approximately 6700 base pairs in mice (Qiao et al 2021). The transcription of MALAT1 is mediated by RNA polymerase II, and the promoter region of this gene is characterized by an open chromatin architecture, which has been demonstrated in various high-throughput studies and DNAase sensitivity assays (Arratia et al 2023).…”
Section: Malat1 Structure and Functionmentioning
confidence: 99%
“…MALAT-1 is another lncRNA which has been shown to be overexpressed in breast and gynecological cancers [ 124 , 125 ]. Specifically, in the cervical cancer cell line CaSki, siRNA-mediated down-regulation reduces proliferation and migration [ 126 ].…”
Section: Enhancer-lncrnas Interactions In Gynecological Cancersmentioning
confidence: 99%
“…For example, a recent study revealed that targeting the MALAT1/PARP1 (poly ADP-ribose polymerase 1) / LIG3 (DNA Ligase 3) complex resulted in DNA damage and apoptosis in multiple myeloma [ 25 ]. In addition, it has been proved that targeting MALAT1 also played a significant role in the treatment of gynecological cancer [ 26 ]. Previous studies have shown that MALAT1 affected cancer through multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%